Effect of boundary shapes of the underlying soil layer on the seismic response of dikes - Nur Arina Binte Ramli (2016)
This paper is an analysis study of simulations for the dynamic response of a dike on varying subsoil shapes using PLAXIS 2D Finite Element Program. Comparisons are made for the values of Peak Ground Acceleration (PGA) and vertical displacement of the dike crest. The dike used in the simulations is a sand-filled dike with a clay core. It has a height of 12 metres, base of 80 metres, and crest span of 8 metres. The dynamic loading inputs are a synthetic harmonic acceleration and an actual earthquake acceleration data. Three effects are analysed – effect of basin shape and depth, effect of basin edge, and effect of basin width. Non-horizontal shaped subsoil profiles results in higher PGA at the dike crest, due to the refraction and amplification of shear waves along the angled slopes. The volume of subsoil in the basin beneath the dike also affects the PGA recorded at the dike crest. A larger volume due to increased depths or wider basin widths contributes to greater amplification of shear waves which results in higher PGA at dike crest. For the study of the effect of basin shape and depth, where the depth increases, the resultant PGA at the dike crest also increases due to the increased volume of subsoil beneath the dike. Trapezoidal shaped subsoil will also results in higher PGA at the dike crest than horizontal shaped subsoil as the angled slopes in the trapezoidal shaped basin allows for refraction and amplification of shear waves. For the study of the effect of basin edge, a more angled slope of 45 degrees of the basin resulted in higher PGA at the dike crest due to the refraction and amplification of shear waves, compared to the angled slope of 5 degrees. For the study of the effect of basin width, wider basins resulted in propagation of shear waves upwards into the subsoil and towards the dike crest. Hence, larger basin widths resulted in higher PGA at dike crest.